Answer:
11x+2
Step-by-step explanation:
Answer:
It may be D, correct me if i'm wrong.
Step-by-step explanation:
We already know that the majority of students will go to a college based on somebody else going to that college. With that in mind, we can draw a cause-and-effect conclusion summarizing why they want to choose that college (Because there friend) and the effect as there friend goes to that college.
<span>Simplifying
(6a + -8b)(6a + 8b) = 0
Multiply (6a + -8b) * (6a + 8b)
(6a * (6a + 8b) + -8b * (6a + 8b)) = 0
((6a * 6a + 8b * 6a) + -8b * (6a + 8b)) = 0
Reorder the terms:
((48ab + 36a2) + -8b * (6a + 8b)) = 0
((48ab + 36a2) + -8b * (6a + 8b)) = 0
(48ab + 36a2 + (6a * -8b + 8b * -8b)) = 0
(48ab + 36a2 + (-48ab + -64b2)) = 0
Reorder the terms:
(48ab + -48ab + 36a2 + -64b2) = 0
Combine like terms: 48ab + -48ab = 0
(0 + 36a2 + -64b2) = 0
(36a2 + -64b2) = 0
Solving
36a2 + -64b2 = 0
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add '64b2' to each side of the equation.
36a2 + -64b2 + 64b2 = 0 + 64b2
Combine like terms: -64b2 + 64b2 = 0
36a2 + 0 = 0 + 64b2
36a2 = 0 + 64b2
Remove the zero:
36a2 = 64b2
Divide each side by '36'.
a2 = 1.777777778b2
Simplifying
a2 = 1.777777778b2
Take the square root of each side:
a = {-1.333333333b, 1.333333333b}</span>